Augmenting Human Connection: A Systematic Review Of Artificial Intelligence In Counseling Practices, Ethics, And Cultural Adaptation - Arjanto, Paul; Makulua, Izak Jakobis; Sampe, Prisca Diantra; Huliselan, Neleke; Ellis, Rusnawati (Jurnal Bimbingan dan Konseling Pandohop, 2026)
The global mental health crisis, intensified by the COVID-19 pandemic, has highlighted significant gaps in access to psychological services, particularly in underserved and low-resource settings. Artificial Intelligence (AI) has emerged as a transformative tool in counseling, offering scalable, personalized, and cost-effective solutions such as chatbot-assisted therapy, affective computing, and AI-driven counselor training. However, its rapid adoption raises ethical and cultural challenges related to empathy, human connection, and algorithmic bias. This study analyzes how AI technologies—specifically chatbots, Natural Language Processing (NLP), and predictive analytics—are applied in counseling practices, focusing on their benefits, limitations, and ethical implications. It also proposes a strategic framework for responsible AI integration across individual, educational, and community counseling contexts. Employing a Systematic Literature Review (SLR) with an integrative qualitative approach, 60 peer-reviewed articles published between 2019 and 2025 were examined. Data were categorized into six themes: chatbot-based therapy, diagnostic tools, counselor education, client perceptions, cultural adaptability, and ethical governance. Findings reveal that while AI performs well in structured tasks such as CBT exercises, mood tracking, and initial assessments, it falls short in addressing complex relational needs like trauma, empathy, and cultural nuance. AI-simulated clients benefit counselor training but risk over-standardizing interpersonal skills. Client trust and satisfaction vary by age, digital literacy, and cultural context. Ethical concerns—such as data privacy, informed consent, and emotional manipulation—are prevalent. This study concludes that AI should complement, not replace, human counseling. It contributes a multidisciplinary synthesis and emphasizes the need for culturally sensitive AI systems, long-term outcome research, and explainable AI (XAI) frameworks for transparency and accountability.